1982
DOI: 10.1007/bf01870765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the plant alkaloid sanguinarine on cation transport by human red blood cells and lipid bilayer membranes

Abstract: The plant alkaloid, sanguinarine, inhibits the ouabain-sensitive K -- Na pump and increases the downhill, ouabain-insensitive movements of K and Na in human red cells. These two effects have different temporal and concentration dependencies and are mediated by two different chemical forms of sanguinarine. The oxidized, charged form (5 X 10(-5) M) promptly inhibits the pump but does not affect leakage of K and Na. The reduced, uncharged form of sanguinarine causes lysis of red cells but does not inhibited the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Our findings may contribute to the elucidation of a more than 30 years old enigma: the related QBA sanguinarine inhibits NKA as well NKP in a variety of tissues [46,47,48,60,61,62] with similar dose dependence as observed here with CET in LECs. Some studies have shown that sanguinarine increases the in vitro dissociation constant of ouabain by 10 fold in guinea pig atrium preparations and exerts an inotropic effect [63], whereas inhibition of 3 H-ouabain binding in beef heart NKA is due to interaction with the ouabain receptor although a conformational change due to direct action was not excluded [46].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings may contribute to the elucidation of a more than 30 years old enigma: the related QBA sanguinarine inhibits NKA as well NKP in a variety of tissues [46,47,48,60,61,62] with similar dose dependence as observed here with CET in LECs. Some studies have shown that sanguinarine increases the in vitro dissociation constant of ouabain by 10 fold in guinea pig atrium preparations and exerts an inotropic effect [63], whereas inhibition of 3 H-ouabain binding in beef heart NKA is due to interaction with the ouabain receptor although a conformational change due to direct action was not excluded [46].…”
Section: Discussionsupporting
confidence: 63%
“…The preliminary observation that clotrimazole and apamin attenuated K + loss suggests that intermediate conductance Ca 2+ -activated K + channels (K + Ca 3.1, IK or Gardos channels) and small conductance SK channels may have been activated by CET. This finding means that the effect of CET in LECs is not due to breaching holes in the membrane bilayer as reported some 30 years ago in sanguinarine -treated human erythrocytes [60]. Interestingly, CET has been shown to block by 73 % the human P2X7 receptor through which extracellular ATP activates cation-selective channels with an IC 50 of 5.6 µM [72].…”
Section: Discussionmentioning
confidence: 53%
“…The CET structure-related sanguinarines have been known for a long time to inhibit the NKP in a variety of tissue preparations [11,12,13,14,15,16,17], without an explanation for this effect. Sequence homologies between BH1-like motifs originally reported to bind CET in Bcl-Xl proteins and found in the cytoplasmic aspect of the crystal structure of the NKP led to the hypothesis that CET may inhibit the NKP function through these BH1 motifs [10].…”
Section: Introductionmentioning
confidence: 99%
“…The observed effect was not due to a decline in lipid cation conductance since Na Fig. 4 higher than that reported for Na + conductance (0.1 mol/l NaCl, pH 7.4) of pure lipid bilayers (Cala et al 1982).…”
Section: Discussionmentioning
confidence: 44%